Effect of Tofacitinib on Hemostasis in Patients with Ulcerative Colitis: A Comparative Ex Vivo Study - Cristina Sánchez-Sánchez; Fabio Suarez-Trujillo; Cristina Ramírez; Irene Soleto; Jorge Mercado; Macarena Orejudo; Paula J. Martínez; Celia Rubio Collado; Mar Orts; María Jesús Rubio Franco; Antonio Planas; Natalia Acedo; et al. (Pharmaceuticals)
Background: Tofacitinib is effective for refractory ulcerative colitis (UC), a chronic inflammatory disease of the colonic mucosa. However, its use has been associated with an increased risk of thromboembolic events, prompting regulatory restrictions. Understanding the pathophysiological mechanisms contributing to these potential risks is critical for patient safety. We aim to evaluate and compare ex vivo the effects of tofacitinib and anti-TNF on coagulation parameters and platelet function. Methods: Whole blood and platelet-rich plasma from 10 active UC (aUC) and 10 quiescent UC (qUC) patients and 10 healthy controls (HC) were spiked ex vivo with tofacitinib, anti-TNF (as comparator), or a sterile solution. Coagulation kinetics were measured by rotational thromboelastometry (ROTEM), platelet aggregation by aggregometry, and platelet activation by flow cytometry. The study was conducted at Hospital Universitario de La Princesa. Results: Flow cytometry showed increased expression of activation markers CD62P and CD63 and higher PAC-1 binding in platelets from both aUC and qUC patients incubated with either tofacitinib or anti-TNF versus no drug. No differences were found between the drugs. CD63 expression also increased in HC after drug exposure, with no differences between anti-TNF or tofacitinib. Platelet aggregation and coagulation parameters did not differ between tofacitinib, anti-TNF, and no drug in aUC, qUC, and HC. Conclusions: Tofacitinib does not alter platelet function or coagulation in UC patients under ex vivo conditions compared to anti-TNF. The increased thromboembolic risk observed in some populations treated with tofacitinib cannot be attributed to these factors in UC patients.